TANTANGAN PENGEMBANGAN ILMU-ILMU USHULUDDIN MENYONSONG PERUBAHAN IAIN AR-RANIRY MENJADI UIN - Wahid, Abdul (UIN Ar-Raniry, 2014)
Theology faculty as the vessel of developing basic Islamic studies that has an important position among the other faculties. The experience of changing institution to be university shown that theology faculty Ã¢â‚¬Å“desertÃ¢â‚¬Â of applicants. Therefore, readiness and progress of Islamic Theology faculty under the State Islamic University (UIN) of course determine the future history of Islamic Theology.This struggle would be faced with all the seriousness of the academic community. Establishing the Faculty of Islamic Theology in the new form to be a demand. On the other hand, the academic communities of Islamic Theology Faculty are required to initiate a new paradigm in the world of work.